Sulfated‐polysaccharide fraction extracted from red algae Gracilaria birdiae ameliorates trinitrobenzenesulfonic acid‐induced colitis in rats. (28th February 2014) - Brito, Tarcisio V.; Neto, José P. R. P.; Prudêncio, Rafael S.; Batista, Jalles A.; Júnior, José S. C.; Silva, Renan O.; Franco, Álvaro X.; Aragão, Karoline S.; Soares, Pedro M. G.; Souza, Marcellus H. L. P.; Chaves, Luciano S.; Freitas, Ana L. P.; et al.
Abstract Objectives The aim of this study was to evaluate the protective effect of the sulfated‐polysaccharide (PLS) fraction extracted from the seaweed Gracilaria birdiae in rats with trinitrobenzenesulfonic acid (TNBS)‐induced colitis. Methods In the experiments involving TNBS‐induced colitis, rats were pretreated with polysaccharide extracted from G. birdiae (PLS: 30, 60 and 90 mg/kg, 500 μL p.o.) or dexamethasone (control group: 1 mg/kg) once daily for 3 days starting before TNBS instillation (day 1). The rats were killed on the third day, the portion of distal colon was excised and washed with 0.9% saline and pinned onto a wax block for the evaluation of macroscopic scores. Samples of the intestinal tissue were used for histological evaluation and assays for glutathione (GSH) levels, malonyldialdehyde (MDA) concentration, myeloperoxidase (MPO) activity, nitrate and nitrite (NO3/NO2) concentration and cytokines levels. Key findings PLS treatment reduced the macroscopic and microscopic TNBS‐induced intestinal damage. Additionally, it avoided the consumption of GSH, decreased pro‐inflammatory cytokine levels, MDA and NO3/NO2 concentrations and diminished the MPO activity. Conclusions Our results suggest that the PLS fraction has a protective effect against intestinal damage through mechanisms that involve the inhibition of inflammatory cell infiltration, cytokine releasing and lipid peroxidation.